Carnitine-acylcarnitine Translocase Deficiency with c.199-10T>G Mutation in Two Filipino Neonates Detected through Parental Carrier Testing - Suzanne Marie G. Carmona; Mary Ann R. Abacan; Maria Melanie Liberty B. Alcausin (MDPI AG, 2023)
Carnitine-acylcarnitine translocase deficiency (CACTD), a fatty acid oxidation defect (FAOD), can present in the neonatal period with non-specific findings and hypoglycemia. A high index of suspicion is needed to recognize the disorder. The case is of a 24-year-old G2P2(2000) mother who sought consultation for recurrent neonatal deaths. The neonates, born two years apart, were apparently well at birth but had a fair cry and no spontaneous eye opening within the first 24 h of life and died before the 72nd hour of life. Newborn screening of both babies revealed elevated long chain acylcarnitines and hypocarnitinemia suggestive of a FAOD. However, due to their early demise, no confirmatory tests were done. Parental carrier testing was performed, revealing both parents to be heterozygous carriers of a pathogenic variant, c.199 10T>G (intronic), in the SLC25A20 gene associated with autosomal recessive CACTD. This is the first reported case of CACTD in the Filipino population.